PENERAPAN MODEL PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Sakinah, Fitri; Fitria, Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Basically, education is an experiment that will never be finished, as long as there is human life in this world, because education is part of human culture and civilization which continues to develop. There are several principles in education, including the process of acculturating and learning students which lasts throughout life on the basis of love. This love is the main capital for teachers who have a dual role and function in the educational process, namely as educators and at the same time as second parents at school. As educators, teachers must use their professionalism in educating, teaching, guiding and directing their students. As parents, teachers must show affection for students as well as for their own children. This requires a process and maximum effort by the teacher as an agent of change. The curriculum is one of the main components of the educational process. The 2013 SD/MI curriculum uses an integrated thematic learning approach. Integrated thematic learning is a learning approach that integrates various competencies from various subjects into various themes. The themes chosen relate to nature and human life and are close to children's lives. Therefore, thematic learning raises themes that are close to students' lives and their environment so that it provides meaning for students because it attracts students' interests and talents so that it helps in completing work or for the students' own future.